2010
DOI: 10.1093/toxsci/kfq054
|View full text |Cite
|
Sign up to set email alerts
|

Irritancy and Allergic Responses Induced by Topical Application of ortho-Phthalaldehyde

Abstract: Although ortho-phthalaldehyde (OPA) has been suggested as an alternative to glutaraldehyde for the sterilization and disinfection of hospital equipment, the toxicity has not been thoroughly investigated. The purpose of these studies was to evaluate the irritancy and sensitization potential of OPA. The EpiDerm Skin Irritation Test was used to evaluate in vitro irritancy potential of OPA and glutaraldehyde. Treatment with 0.4125 and 0.55% OPA induced irritation, while glutaraldehyde exposure at these concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 26 publications
1
56
0
Order By: Relevance
“…This strain was selected because these mice are good IgE producers and have historically been used in the laboratory to evaluate chemical sensitization (Anderson et al, 2010). Mice were housed at a maximum of five per cage in ventilated plastic shoebox cages with hardwood chip bedding, NIH-31 modified 6% irradiated rodent diet (Harlan Teklad), and filtered tap water (ad libitum).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…This strain was selected because these mice are good IgE producers and have historically been used in the laboratory to evaluate chemical sensitization (Anderson et al, 2010). Mice were housed at a maximum of five per cage in ventilated plastic shoebox cages with hardwood chip bedding, NIH-31 modified 6% irradiated rodent diet (Harlan Teklad), and filtered tap water (ad libitum).…”
Section: Animalsmentioning
confidence: 99%
“…Olive oil has poly-ols and therefore the stability of free diisocyanate in olive oil would be a concern. This vehicle control has also historically been used in our laboratory to evaluate chemical sensitization (Anderson et al, 2010;Franko et al, 2012).…”
Section: Tdi Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Elicitation of irritant and allergic reactions in mice has been reported [Anderson et al 2010;Morinaga et al 2010]. More recently, other investigators have found that inhalation of OPA vapors in mice can trigger both respiratory and systemic sensitization.…”
Section: Ortho-phthalaldehydementioning
confidence: 99%
“…We were not able from our PST and OPA-specific IgE results to determine if either method was an accurate measure of OPA sensitization. A laboratory study in mice showed that dermal OPA exposure resulted in dermal irritation and potential sensitization [Anderson 2010]. Topical application of OPA to mice also resulted in significant increases in total IgE, OPA-specific IgE, and OPA-specific IgG 1 [Anderson et al 2010].…”
Section: Puncture Skin Tests and Antibody Immunoassaysmentioning
confidence: 99%